The location of the inferior alveolar nerve in the malaysian population: Implications for dental implant planning - Sujaysen R Kumar; Pravinkumar G Patil; Chan S Choy; Abhi Veerakumarasivam (Wolters Kluwer Medknow Publications, 2020)
Background: The location of the inferior alveolar nerve (IAN) is generally constant in fully grown mandibles. If we know its average distance from the lower border of the mandible, available bone length from the crest of the edentulous ridge can be estimated by physical measurement of the whole length of mandible in that area. This study aimed to measure the superio-inferior distance of the inferior alveolar nerve (SIDIAN) from the base of the mandible in posterior regions on the right and left side based on cone-beam-computed tomography (CBCT) scans and to evaluate gender and ethnicity-related variations in the Malaysian population. Materials and Methods: A total of 100 CBCT-Digital Imaging and Communications in Medicine files of the patients of 3 ethnic populations (Malay, Chinese and Indian) between the ages of 18 and 80 years were selected for the study. The files were imported onto the iCAT software. The measurements of the SIDIAN to the lower border of the mandible in molar regions were done on both sides. The data was analysed using t-test, one-way analysis of variance test, and correlation coefficient test via the SPSS software. Results: Statistically significant positive correlations were identified between the SIDIAN from the lower border of the mandible in the first and second molar regions within the same side as well as between both sides of the mandible (r ≈ 0.8). There were no statistically significant differences between genders. However, there were statistically significant differences on both molar regions and on both sides in all three ethnic groups (P < 0.05). In general, the SIDIAN from the lower border of the mandible was greatest amongst Chinese and smallest amongst Indians. Conclusions: The strong positive correlations on both sides of the mandible indicate the presence of symmetry. Ethnicity-related variations exist in terms of the location of the IAN in the mandible.